2019
DOI: 10.1016/j.heliyon.2019.e01552
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin derivatives as acetyl- and butyrylcholinestrase inhibitors: An in vitro, molecular docking, and molecular dynamics simulations study

Abstract: Alzheimer's disease is an irreversible and progressive brain disease that can cause problems with memory and thinking skills. It is characterized by loss of cognitive ability and severe behavioral abnormalities, and could lead to death. Cholinesterases (ChEs) play a crucial role in the control of cholinergic transmission, and subsequently, the acetylcholine level in the brain is upgraded by inhibition of ChEs. Coumarins have been shown to display potential cholinesterase inhibitory action, where the aromatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…This disease is becoming a universal health problem, and it can eventually lead to death [ 48 ]. Statistics indicate the presence of approximately 2.5 to 4.0 million Alzheimer’s disease patients in the United States, and 17 and 25 million worldwide [ 49 ]. Published research findings indicate that cholinergic dysfunction could be associated with selective and irreversible deficiency of the neurotransmitter acetylcholine, which is controlled by hydrolysis of acetylcholine via acetylcholinestrase (AChE) and butyrylcholinestrase (BChE).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This disease is becoming a universal health problem, and it can eventually lead to death [ 48 ]. Statistics indicate the presence of approximately 2.5 to 4.0 million Alzheimer’s disease patients in the United States, and 17 and 25 million worldwide [ 49 ]. Published research findings indicate that cholinergic dysfunction could be associated with selective and irreversible deficiency of the neurotransmitter acetylcholine, which is controlled by hydrolysis of acetylcholine via acetylcholinestrase (AChE) and butyrylcholinestrase (BChE).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Published research findings indicate that cholinergic dysfunction could be associated with selective and irreversible deficiency of the neurotransmitter acetylcholine, which is controlled by hydrolysis of acetylcholine via acetylcholinestrase (AChE) and butyrylcholinestrase (BChE). Additionally, it was suggested that AChE predominates in a healthy brain, whereas BChE is considered to play a minor role in regulating the brain’s ACh levels [ 49 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…The Asp70 residue interacts with the tripeptide CIK by two salt bridges and a carbon‐hydrogen bond, and Tyr332 residue forms a conventional hydrogen bond and a pi‐alkyl with the tripeptide CIK. These two residues are essential for substrate‐enzyme binding . The interaction between CIK and BACE1 involves the following amino acid residues: Ile110, Thr232, Gly230, Thr231, Arg235, Thr72, Gly34, Asp228, and Asp32 (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These two residues are essential for substrate-enzyme binding. 34 The interaction between CIK and BACE1 involves the following amino acid residues: Ile110, Thr232, Gly230, Thr231, Arg235, Thr72, Gly34, Asp228, and Asp32 (shown in Fig. 4).…”
Section: Validation Of Activity Of Peptides Against Ache Bche and Bace1mentioning
confidence: 99%
“…Jannat et al reported that (2 S ,3 R )-pretosin C is a noncompetitive inhibitor of BChE and that it hydrophobically interacts with Val288, Lue286, and Phe357, and hydrogen bonds with Gly283 and Asn397, and docks at a non-ligand binding site [ 56 ]. It was also observed that hydrogen bond formation was the main driving force behind BChE–coumarin complex formation, whereas hydrophobic and halogen interactions underpinned AChE interactions with N 1-(coumarin-7-yl) derivatives [ 57 ]. Similarly, we found that GC hydrogen bonded with Thr284 and Val288 located outside the ligand binding site.…”
Section: Discussionmentioning
confidence: 99%